UCLA PTSD reaction index for DSM-5 (PTSD-RI-5): a psychometric study of adolescents sampled from communities in eleven countries - Doric, Ana (2021)
Background: Children and adolescents are often exposed to traumatic events, which may lead to the development of posttraumatic stress disorder (PTSD). It is therefore important for clinicians to screen for potential symptoms that can be signs of PTSD onset. PTSD in youth is a worldwide problem, thus congruent screening tools in various languages are needed. Objective: The aim of this study was to test the general psychometric properties of the Traumatic Stress Disorder Reaction Index for children and adolescents (UCLA PTSD) Reaction Index for DSM-5 (PTSD-RI-5) in adolescents, a self-report instrument intended to screen for trauma exposure and assess PTSD symptoms. Method: Data was collected from 4201 adolescents in communities within eleven countries worldwide (i.e. Brazil, Bulgaria, Croatia, Indonesia, Montenegro, Nigeria, Palestine-Gaza, Philippines, Portugal, Romania, and Serbia). Internal consistency, discriminant validity, and a confirmatory factor analysis of a four-factor model representing the main DSM-5 symptoms of the PTSD-RI-5 were evaluated. Results: The PTSD-RI-5 total score for the entire sample shows very good reliability (α = .92) as well as across all countries included (α ranged from .90 to .94). The correlations between anxiety/depressive symptoms and the PTSD-RI-5 scores were below .70 indicating on good discriminant validity. The four-factor structure of the scale was confirmed for the total sample and data from six countries. The standardized regression weights for all items varied markedly across the countries. The lack of a common acceptable model across all countries prevented us from direct testing of cross-cultural measurement invariance.Conclusions: The four-factor structure of the PTSD-RI-5 likely represents the core PTSD symptoms as proposed by the DSM-5 criteria, but there could be items interpreted in a conceptually different manner by adolescents from different cultural/regional backgrounds and future cross-cultural evaluations need to consider this finding. HIGHLIGHTS • The cross-cultural aspects of the DSM-5 PTSD reaction index for youth (PTSD-RI-5) across multiple, worldwide countries were addressed • The four-factor structure of the scale that follows the DSM-5 criteria for PTSD was confirmed • Not all PTSD symptoms as measured by the instrument are relevant to adolescents across different societies. Antecedentes: Los niños y adolescentes a menudo están expuestos a eventos traumáticos, que pueden llevar al desarrollo de un trastorno de estrés postraumático (TEPT). Por lo tanto, es importante que los médicos examinen los posibles síntomas que pueden ser signos del inicio de un TEPT. Este trastorno en jóvenes es un problema global, por lo que se necesitan herramientas de detección congruentes en varios idiomas. Objetivo: El objetivo de este estudio fue probar en adolescentes las propiedades psicométricas generales del Índice de Reacción TEPT de la UCLA para el DSM-5 (PTSD-RI-5), que es un instrumento de auto-reporte destinado a evaluar la exposición al trauma y evaluar los síntomas de PTSD.